Validity and reliability of the Korean version of the Speech Handicap Index in patients with oral cavity cancer. Issue 4 (April 2016) - Park, S.S.; Choi, S.H.; Hong, J.A.; Hong, Y.H.; Jeong, N.G.; Lee, S.Y.; Sung, M.-W.; Hah, J.H.
Abstract: The aims of this study were to evaluate the cross-cultural adaptation of the Speech Handicap Index (SHI) for Korean subjects and to determine its reliability and utility in patients with oral cavity cancer. The Korean version of the SHI was administered to 50 healthy subjects and 56 patients with speech problems resulting from treatment for oral cavity cancers. The content and construct validity, internal consistency, and test–retest reliability were examined. Healthy subject and patient group scores were compared, and the Mann–Whitney U -test was used to determine discriminatory ability. The Korean version of the SHI had high internal consistency (Cronbach's alpha = 0.99) and test–retest reliability for the total and subscales: total (T) 0.98, speech (S) 0.99, and psychosocial (P) 0.97. Mean scores in the healthy group were 0.5 (T), 0.2 (S), and 0.2 (P), whereas those in the patient group were 34.3 (T), 16.6 (S), and 15.5 (P). The scores differed significantly between the groups ( P  < 0.05). The Korean version of the SHI can be a useful tool to evaluate a patient's self-perception of their speech dysfunction in daily life and to better understand postoperative speech disorders in patients with oral cavity cancer.